2017
DOI: 10.1002/adom.201600941
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Stokes Shift with Strong Coupling

Abstract: A stronger coupling can be achieved if a molecule is placed into a small resonant Fabry-Perot cavity or to a vicinity of a nanostructure supporting surface plasmon (SP) resonance. The time evolution of the two coupled oscillators, e.g., a cavity and a molecule, can be described as a linear superposition of their normal hybrid modes. [4] The even (odd) oscillation mode has the higher (lower) frequency, ω ± = ω 0 ± Δ, and corresponds to the upper (lower) branch of the dispersion curve. (Here Δ is the coupling fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…In particular, it has been shown recently that chemical reactivity (19,(23)(24)(25) and charge and exciton transport (26)(27)(28) can be modified under strong coupling conditions. Strong coupling has been demonstrated to tune the work-function (29), as well as to control the Stokes shifts of hybridized molecules (30). Feist et al (24) have theoretically described an increased stability in the strong coupling regime for a photo-isomerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown recently that chemical reactivity (19,(23)(24)(25) and charge and exciton transport (26)(27)(28) can be modified under strong coupling conditions. Strong coupling has been demonstrated to tune the work-function (29), as well as to control the Stokes shifts of hybridized molecules (30). Feist et al (24) have theoretically described an increased stability in the strong coupling regime for a photo-isomerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that when dye molecules are strongly coupled to a cavity, the emission originating from the low‐energy polariton branch is not observed when the system is pumped into the same branch. This effect was explained in terms of parity forbidden transitions within the same excited state parabola. The same arguments should be applicable to the transition between the low‐energy polariton branch of the hybridized S 2 state and the low‐energy polariton branch of the hybridized S 1 state.…”
Section: Resultsmentioning
confidence: 99%
“…The used amounts of R6G and PMMA resulted in the dye concentration (in solid state) equal to 2.69 × 10 20 cm −3 , equivalent to 313 g L −1 or 7.99 × 10 −2 mol/L (see ref. for calculation of the dye concentration).…”
Section: Methodsmentioning
confidence: 99%
“…Light fields in microcavities can contribute to ≈20‐fold enhancement for low finesse cavities, up to as much as ≈400‐fold for high finesse cavities. Therefore, scattered and incident Raman scattering field effects can be enhanced, enhancing Raman cross sections several hundred folds compared to common effects …”
Section: Strong Coupling Practical Applicationsmentioning
confidence: 99%